Appraisal and ideology in students’ argumentative texts: a systemic functional linguistics study - Risdianto, Faizal; Nugroho, Haryo Aji; Sunardi, Sunardi; Arkida, Teisar (JOALL (Journal of Applied Linguistics and Literature), 2025)
This study aims to examine how students employ evaluative language in argumentative writing using Appraisal theory, specifically the categories of Attitude, Graduation, and Engagement to uncover the connection between evaluative strategies and ideological positioning, a relatively unexplored area in EFL research. Employing a mixed-methods design, the study analysed argumentative essays and survey responses from participants in the 2024 Argumentative Writing Contest. Data were collected from 21 submissions, with four texts selected based on argumentative quality, linguistic richness, and regional representation (Bengkulu, Kotawaringin, Bekasi, and Yogyakarta). A survey questionnaire accompanied the text analysis to gather student insights on their writing experiences. The textual data from students’ writings were examined using the Appraisal framework in systemic functional linguistics (SFL), and the survey data from the questionnaire were processed through the interactive analysis model in qualitative research, involving data condensation, display, and verification. Triangulation and member checking ensured data credibility. Findings revealed that students’ evaluative language mainly utilized appreciation to represent ideological stance and assessing regional learning environments. Most of the writers used intensifier markers, while students from remote regions used more monoglossic expressions. Cultural norms shaped argumentation styles, with some preferring indirect persuasion. This suggests that evaluative writing is both linguistically and culturally situated. The study’s implications advocate for culturally responsive and linguistically targeted instruction to bridge regional disparities in argumentative writing competence.